The Dynamics of Transpiration to Evapotranspiration Ratio under Wet and Dry Canopy Conditions in a Humid Boreal Forest - Bram Hadiwijaya; Steeve Pepin; Pierre-Erik Isabelle; Daniel F. Nadeau (Forests, 2020)
Humid boreal forests are unique environments characterized by a cold climate, abundant precipitation, and high evapotranspiration. Transpiration ( E T ), as a component of evapotranspiration (E), behaves differently under wet and dry canopy conditions, yet very few studies have focused on the dynamics of transpiration to evapotranspiration ratio ( E T / E ) under transient canopy wetness states. This study presents field measurements of E T / E at the Montmorency Forest, Québec, Canada: a balsam fir boreal forest that receives ∼ 1600 mm of precipitation annually (continental subarctic climate; Köppen classification subtype Dfc). Half-hourly observations of E and E T were obtained over two growing seasons using eddy-covariance and sap flow (Granier’s constant thermal dissipation) methods, respectively, under wet and dry canopy conditions. A series of calibration experiments were performed for sap flow, resulting in species-specific calibration coefficients that increased estimates of sap flux density by 34 % ± 8 % , compared to Granier’s original coefficients. The uncertainties associated with the scaling of sap flow measurements to stand E T , especially circumferential and spatial variations, were also quantified. From 30 wetting–drying events recorded during the measurement period in summer 2018, variations in E T / E were analyzed under different stages of canopy wetness. A combination of low evaporative demand and the presence of water on the canopy from the rainfall led to small E T / E . During two growing seasons, the average E T / E ranged from 35 % ± 2 % to 47 % ± 3 % . The change in total precipitation was not the main driver of seasonal E T / E variation, therefore it is important to analyze the impact of rainfall at half-hourly intervals.